Individual differences in self-affirmation: Distinguishing self-affirmation from positive self-regard. Issue 6 (2nd November 2019) - Harris, Peter R.; Griffin, Dale W.; Napper, Lucy E.; Bond, Rod; Schüz, Benjamin; Stride, Christopher; Brearley, Irina
ABSTRACT: Research into self-affirmation has almost exclusively employed experimental manipulations. In this paper we address individual differences in the tendency to respond to threats with self-affirming cognitions and distinguish this from two overlapping constructs: habitual positive self-thought and trait self-esteem. Items we designed to measure self-affirmation were represented by three first-order factors and loaded on a higher-order factor, creating the Spontaneous Self-Affirmation Measure (SSAM). The SSAM correlated moderately with self-esteem and habitual positive self-thought. In competitive analyses, the SSAM was an independent predictor of a large number of outcomes. The studies provide evidence about the correlates of individual differences in reported spontaneous self-affirmation in response to threat and the contribution made to this response by habitual positive self-thought and trait self-esteem.